The Concept of Order and the Development of Theatre Art - Bitinaitė-Širvinskienė, Raimonda (Respectus Philologicus, 2006)
The article analyzes the place of theatre art in a theatre system. Applying the sociological model, it attempts to explicate the ability of scenography to maintain or change the order in the multilayer theatre structure the predominance of hierarchical order. The aim of the article is to demonstrate the flexible position of the theatre art in theatre community.
Keywords: theatre art; order; chaos; structure